2016
DOI: 10.1103/physreva.93.063830
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of chiral quantum optics with Rydberg and trapped-ion setups

Abstract: We propose two setups for realizing a chiral quantum network, where two-level systems representing the nodes interact via directional emission into discrete waveguides, as introduced in T. Ramos et al. [Phys. Rev. A 93, 062104 (2016)]. The first implementation realizes a spin waveguide via Rydberg states in a chain of atoms, whereas the second one realizes a phonon waveguide via the localized vibrations of a string of trapped ions. For both architectures, we show that strong chirality can be obtained by a pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 92 publications
(200 reference statements)
0
67
0
Order By: Relevance
“…Finally, we summarized recent applications of this theoretical framework to the description of exotic many-body phases [18] and unconventional Rydberg blockade [19], both of them being relevant for the interpretation of on-going and future experiments. The possibilities given by these rich and complex properties of the Rydberg interactions are manifold: observation of topological states of matter [26], implementation of exotic spin models [33,34], new types of interactions between Rydberg polaritons [35], or the implementation of chiral spin-wave guides, where Rydberg excitations propagate along a chain of atoms along a preferential direction [36].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we summarized recent applications of this theoretical framework to the description of exotic many-body phases [18] and unconventional Rydberg blockade [19], both of them being relevant for the interpretation of on-going and future experiments. The possibilities given by these rich and complex properties of the Rydberg interactions are manifold: observation of topological states of matter [26], implementation of exotic spin models [33,34], new types of interactions between Rydberg polaritons [35], or the implementation of chiral spin-wave guides, where Rydberg excitations propagate along a chain of atoms along a preferential direction [36].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the mirror-like behavior of the chain could be used to realize a chiral quantum network, where atoms interact via one-way emission [7][8][9]. It could also be used as an optical reflector or an optical mirror to create, together with a distant dielectric mirror, a Fabry-Pérot cavity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Another kind of systems that can exhibit mirror properties or equivalently a highly directive radiative properties are atoms chirally coupled to a waveguide [7,8]. Chirality in atom-waveguide coupling is an effect associated with a broken symmetry of emission of photons from the atoms into the * qgulfam@jazanu.edu.sa † zficek@kacst.edu.sa right and left propagating modes of the waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that substantial coupling between two atoms can survive over long interatomic distances due to guided modes [26]. The chiral coupling between atoms has been studied in the framework of one-dimensional waveguide bath models [40][41][42][43][44][45][46], where radiation modes were completely [40][41][42][43][44] or partially [45,46] neglected. In closely related studies, the chiral effect in spontaneous emission of a single atom [47] and the radiative transfer between two atoms [48] in front of a dielectric surface have also been investigated.…”
Section: Introductionmentioning
confidence: 99%